Private Ownership of Marine Territories in Sumba: Cultural Identity, Globalization, and Algorithmic Power in the Struggles of Coastal Communities - Eva Solina Gultom (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2025)
The extension of private land ownership into marine territories in Sumba has generated socio-economic tensions by restricting traditional fishing grounds and undermining communal access to coastal resources; yet, scholarly attention to its cultural and digital implications remains limited. This study aims to examine how such privatization affects the livelihoods and cultural identity of coastal communities in the context of globalization and algorithmic power. Employing a qualitative ethnographic approach combined with digital discourse analysis, the research investigates community narratives, policy documents, and representations across social media platforms. The findings reveal that privatization disrupts indigenous systems of reciprocity, compels local communities to renegotiate their cultural identity, and exposes them to global economic models that privilege individual ownership. Moreover, algorithmic amplification in digital media tends to marginalize indigenous voices while reinforcing dominant narratives aligned with commercial interests. The study concludes that marine privatization in Sumba not only reshapes socio-cultural relations but also illustrates how globalization and algorithmic systems jointly reconfigure cultural identity and resource legitimacy in contemporary Indonesia.